2022
DOI: 10.3389/fphys.2022.1009607
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent alteration in the chemoreflex post-acute lung injury

Abstract: Acute lung injury (ALI) induces inflammation that disrupts the normal alveolar-capillary endothelial barrier which impairs gas exchange to induce hypoxemia that reflexively increases respiration. The neural mechanisms underlying the respiratory dysfunction during ALI are not fully understood. The purpose of this study was to investigate the role of the chemoreflex in mediating abnormal ventilation during acute (early) and recovery (late) stages of ALI. We hypothesized that the increase in respiratory rate (fR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This results in improper gas exchange leading to increased breathing frequency and eventually, hypoxemia, thus, activating a chemoreflex response during ALI ( Bernard et al, 1994 ; Jacono et al, 2006 ; Spinelli et al, 2020 ). Furthermore, we have previously shown that there were enhanced fR responses to both hypoxia and normoxia-hypercapnia at W4 post-bleo even after the resting f R is restored to the normal range ( Kamra et al, 2022 ). Our current data in Figures 5 , 6 further recapitulated this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in improper gas exchange leading to increased breathing frequency and eventually, hypoxemia, thus, activating a chemoreflex response during ALI ( Bernard et al, 1994 ; Jacono et al, 2006 ; Spinelli et al, 2020 ). Furthermore, we have previously shown that there were enhanced fR responses to both hypoxia and normoxia-hypercapnia at W4 post-bleo even after the resting f R is restored to the normal range ( Kamra et al, 2022 ). Our current data in Figures 5 , 6 further recapitulated this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia resulting from ALI stimulates carotid bodies (CBs) to induce a reflexive increase in respiratory rate (fR) (i.e., chemoreflex), which is a fundamental protective mechanism that maintains oxygen homeostasis ( Bernard et al, 1994 ; Jacono et al, 2006 ; Spinelli et al, 2020 ). Our laboratory has previously demonstrated that while f R recovers, the chemoreflex remains chronically sensitized during the recovery from ALI ( Kamra et al, 2022 ). The chemoreflexes are important modulators of sympathetic activation.…”
Section: Introductionmentioning
confidence: 99%